Antibacterial and Antioxidant Studies of Green Synthesized Silver Nanoparticles using Azadirachta indica (Neem) Leaf Extract - Regmi, Bishow; Binadi, Tirtha Raj; Jha, Sarb Narayan; Chaudhary, Rajib Kumar; Poudel, Bhoj Raj; Gautam, Surendra Kumar (International Journal of Applied Sciences and Biotechnology, 2021)
Silver nanoparticles (AgNPs) have been synthesized by green synthesis using Azadirachta indica leaf extract as both reducing and stabilizing agent. Synthesis of colloidal AgNPs was monitored by UV- visible spectroscopy. The UV- visible spectrum showed a peak at 455 nm corresponding to the plasmon absorbance of the silver nanoparticles. Crystallite structure of silver nanoparticles was studied using X-ray diffraction (XRD) analysis which revealed the face-centered cubic structure (FCC) with average particle size of 8.9 nm, calculated using Debye-Scherrer’s equation. Transmission electron microscopy (TEM) image revealed the agglomeration of small grain with particle size ranging from 2 to 14 nm. FCC crystalline nature was also evident from selected area electron diffraction (SAED) analysis. High purity of as-synthesized AgNPs was analyzed using energy dispersive X-ray (EDX) spectroscopy. Band gap energy was calculated to be 2.7 eV from UV- Visible spectra. 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay was stabilized by AgNPs which reveals its antioxidant efficacy. Well diffusion method showed 7 mm to 12 mm zone of inhibition (ZOI) against Gram-positive and Gram-negative bacteria, respectively confirming the antibacterial potential of AgNPs.Int. J. Appl. Sci. Biotechnol. Vol 9(3): 220-226.